2022
DOI: 10.1097/cce.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Modifiable Postresuscitation Management and Annual Case Volume With Survival After Extracorporeal Cardiopulmonary Resuscitation

Abstract: IMPORTANCE:It is not know if hospital-level extracorporeal cardiopulmonary resuscitation (ECPR) case volume, or postcannulation clinical management associate with survival outcomes. OBJECTIVES:To describe variation in postresuscitation management practices, and annual hospital-level case volume, for patients who receive ECPR and to determine associations between these management practices and hospital survival.DESIGN: Observational cohort study using case-mix adjusted survival analysis. SETTING AND PARTICIPANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 48 publications
0
41
1
Order By: Relevance
“…However, others revealed a minor or no effect on survival 17,25 . Such conflicting results probably arose from the heterogeneity in the strength of the chain of survival, patient selection criteria, adopted strategy, logistical organization, center experience, and post‐resuscitation care practice (e.g., advanced circulatory and ventilatory support, temperature management, and prognostication/withdrawal of life‐support therapy), leading to highly variable survival rates 26 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, others revealed a minor or no effect on survival 17,25 . Such conflicting results probably arose from the heterogeneity in the strength of the chain of survival, patient selection criteria, adopted strategy, logistical organization, center experience, and post‐resuscitation care practice (e.g., advanced circulatory and ventilatory support, temperature management, and prognostication/withdrawal of life‐support therapy), leading to highly variable survival rates 26 …”
Section: Discussionmentioning
confidence: 99%
“…Implementing extracorporeal CPR in different settings and healthcare systems might fail to reproduce the beneficial effect observed in this meta‐analysis or single‐center RCTs. Moreover, a strong relationship exists between center experience with extracorporeal CPR, estimated by the annual case volume, and outcomes 26 . In the process of implementing extracorporeal CPR, centers should critically assess their logistics and monitor the program's performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the Extracorporeal Life Support Organization (ELSO) registry suggested that survival after ECPR was associated with modifiable post‐resuscitation practices and center volume 13 . Likewise, low volume per center, absence of standardization, and delays in how ECPR was provided in the INCEPTION trial may have contributed to its reduced effect, being, per definition, a time‐dependent intervention.…”
Section: Ecpr Is a Complex Interventionmentioning
confidence: 99%